2019
DOI: 10.1007/s00520-019-04729-w
|View full text |Cite
|
Sign up to set email alerts
|

Body changes after cancer: female cancer patients’ perceived social support and their perspective on care

Abstract: PurposeThe aim of this study was to investigate among female cancer patients their perceived social support from health care professionals (HCPs), family and friends, and public media, and their perspective on care concerning body changes.MethodsA study-specific questionnaire was completed by 235 female cancer patients. Descriptive statistics were used to describe social support and perspective on care. Logistic regression analyses were used to investigate the associations between social support and sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Perceived social support (PSS) is one of the important aspects of care for oncology patients (Kelley et al., 2019). Social support initiates with social contact, communication and safe support for the individual (Melissant et al., 2019). Effective social support helps individuals to cope with the stressful conditions and can lead to a better feeling towards themselves (Abadi Bavil & Dolatian, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Perceived social support (PSS) is one of the important aspects of care for oncology patients (Kelley et al., 2019). Social support initiates with social contact, communication and safe support for the individual (Melissant et al., 2019). Effective social support helps individuals to cope with the stressful conditions and can lead to a better feeling towards themselves (Abadi Bavil & Dolatian, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mental, and physical burden were also connected to each other, as side effects (Gouzman et al, 2015), and low urinary symptoms also showed (Lin et al, 2020). Previous studies have shown that patients are interested in the side effects of their treatment (Beusterien et al, 2013) as well as practical (Ran et al, 2016;Melissant et al, 2019) and psychosocial support (Dubey et al, 2015;Perl et al, 2016). Some of the research covered in this review demonstrated how an intervention aiming to help in practical self-care issues and develop coping strategies can ease mental and physical burden, as well as improve resilience (Lin et al, 2020;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Surviving any cancer requires mental and physical strength. The side effects of treatment (Karimi et al, 2017), changes in body image (Bulkley et al, 2013;Melissant et al, 2019), and fear of recurrence (Willems et al, 2016;Hall et al, 2018) can all considerably affect a cancer patient's health and overall quality of life (Ye et al, 2017). Colorectal cancer patients are a unique group with unique needs.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, illness often becomes visible with the beginning of treatment, which is experienced as a period of body deterioration (Quintard and Lakdja, 2008) and loss of social and emotional identity (Amiel et al, 2009). Analogously, surgery can deeply affect body image and self-esteem (Callahan, 2005;Melissant et al, 2019), which are negatively associated with a decline in quality of life (Manos et al, 2005). Surgery can damage body integrity with scars or even permanently alter highly visible body parts (e.g., head and neck surgery), functional organs (e.g., colorectal surgery) and symbols of femininity (e.g., breast surgery).…”
Section: Self-esteem and Cancermentioning
confidence: 99%